Am I typing fresh tweets: Detecting up-to-dateness and worth of categorical information in microblogs. Issue 12 (15th July 2015) - Cingiz, Mustafa Özgür; Diri, Banu; Biricik, Göksel
Highlights We compare bot & normal user tweets and check their up-to-dateness by using RSS feeds. We evaluate the relevance of tweet contents to the categorical taxonomies of users. Longer tweets of bot users reflect their categories better than normal users. Referring to RSS news feeds, content provided by bot users is more up-to-date.